2007
DOI: 10.1007/s00167-007-0291-2
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic adhesive capsulitis of the shoulder: a review

Abstract: Many terms have been used to describe what has been called idiopathic adhesive capsulitis of the shoulder. This pathology is defined as a self-limiting condition of unknown etiology. The natural history is 18-30 months even though a high-percentage of patient present impaired range of movement even at long-term follow-up. The diagnosis is mainly clinical and no significant changes are normally present at MRI or CT scan. Several treatment options have been tried over the years with different approaches and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 50 publications
2
137
0
2
Order By: Relevance
“…Radiographs are often normal in adhesive capsulitis but may show some decreased bone mineral density [3]; however, in this case, there is a clear lytic lesion in the humeral head and neck on the plain Wlms. It is unclear whether these Wlms were reported by a radiologist.…”
mentioning
confidence: 69%
“…Radiographs are often normal in adhesive capsulitis but may show some decreased bone mineral density [3]; however, in this case, there is a clear lytic lesion in the humeral head and neck on the plain Wlms. It is unclear whether these Wlms were reported by a radiologist.…”
mentioning
confidence: 69%
“…23,32 The patient's shoulder condition described in this case best matched a stage 2 presentation. Although adhesive capsulitis is considered to involve primarily the capsular tissue, 1,3,6,25 the pain the patient experienced was most likely due to myofascial trigger points, indicating that the synovitis stage had resolved. Furthermore, significant gains in ROM after the pain was reduced suggest that capsule fibrosis, which is characteristic of stage 3, had likely not developed.…”
Section: Discussionmentioning
confidence: 99%
“…Active shoulder ROM was not measured during this session. Treatment Session 6 The patient reported that her pain level after the previous treatment and at rest was 2/10 on the NPRS. This pain was described as unfamiliar muscle soreness in the upper trapezius and deltoid, in the areas where dry needling was performed.…”
Section: Interventionmentioning
confidence: 99%
“…[6,21] While there are investigators who accept concomitant diseases such as diabetes and hyperthyroidism as also being idiopathic, others consider these to be secondary to AC. [6,21,22] In this study, the rate of concomitant diabetes was 31.7% in the AC group and 11.7% in the SIS group.…”
Section: Discussionmentioning
confidence: 99%